De la frontera política a las fronteras étnicas: refugiados guatemaltecos en México - Edith F. Kauffer Michel (El Colegio de la Frontera Norte, 2005)
This work tries to apply the various meanings of the term frontera (border) (understood as a boundary, as colonizations front line, and as a symbolic and an ethnic divide) to the life experiences of Guatemalan refugees in Mexico, which unfolds in two phases: asylum and integration. An analysis of information gathered from fieldwork during these two processes lays bare the prominence, in the first phase, of the border as a political boundary, whereas prevalence of ethnic divisions characterizes the second phase, as the former refugees and Mexicans who were interviewed revealed.